Preparing the STEM workforce for the global semiconductor industry: International education, economic development, and national security - McKeown, Joshua S. (American Journal of STEM Education, 2026)
The global semiconductor industry has become central to economic competitiveness, technological innovation, and national security. As governments invest heavily in semiconductor manufacturing and supply chain resilience, higher education institutions play a critical role in preparing a globally competent STEM workforce. This study presents a case study of two public higher education institutions in New York State that developed international education initiatives to support workforce development in the emerging semiconductor ecosystem. Through partnerships with universities in key semiconductor regions, including South Korea and Taiwan, the program integrates STEM education, international learning, and industry engagement.